Hypothesis Testing and Life Expectancy: A Review (JOURNAL OF SOFTWARE ENGINEERING TOOLS & TECHNOLOGY TRENDS, 2023)
Data science revolves around the idea of making moves/choices on the basis of past information available. However, data in itself is a broader term. There is raw data, which is collected by using survey and other methods, it may contain the information we need, but it also contains various other non-required information which is removed from the raw data by processing it. The data now recovered is vital information. Data Science is used in predicting trends and forecasting events. Hypothesis testing combines both at a fundamental level and is quite easy to understand and begin with. In addition to that, the testing involves methods currently being taught in our syllabus; so, a side-by-side application helps open our minds towards the subject.